1993
DOI: 10.1111/j.1464-410x.1993.tb16076.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Histological Review on Clinical Management of Testicular Cancer

Abstract: Accurate histological diagnosis and staging are critically important in determining the optimal management of patients with testicular cancer. We have assessed the importance of histological review of "outside" pathology reports from 87 patients referred to the Urological Cancer Research Unit. In 28 patients (32%), the reviewed pathology report differed from the outside report. In 10 of these patients (11%), the pathology review resulted in a change of treatment or prognosis from that which would have obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 3 publications
3
12
0
Order By: Relevance
“…Studies addressing the impact of central histopathologic review of previously diagnosed testicular tumors have demonstrated major discrepancy rates of 4-11%, with the majority of discrepancies attributed to errors in distinguishing seminoma from embryonal carcinoma. [23][24][25] The use of immunohistochemistry may therefore be of value in differentiation of these tumor types.…”
Section: Resultsmentioning
confidence: 99%
“…Studies addressing the impact of central histopathologic review of previously diagnosed testicular tumors have demonstrated major discrepancy rates of 4-11%, with the majority of discrepancies attributed to errors in distinguishing seminoma from embryonal carcinoma. [23][24][25] The use of immunohistochemistry may therefore be of value in differentiation of these tumor types.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Indeed, studies demonstrating the value of central histologic review of previously diagnosed testicular malignancies have shown most discrepancies to be the result of errors in distinguishing seminoma from embryonal carcinoma. [19][20][21] The use of immunohistochemical study may therefore be of value in differentiation of these entities.…”
Section: Discussionmentioning
confidence: 99%
“…Expert pathology review has been shown to be important in the diagnosis of cancer at any age (Presant et al, 1986;Segelov et al, 1993). For example , Segelov et al (1993), in their review of adult testicular tumours, found that in 28 out of 87 (32%) patients, the diagnosis made on referral to the specialist centre differed from the original.…”
Section: Discussionmentioning
confidence: 99%
“…For example , Segelov et al (1993), in their review of adult testicular tumours, found that in 28 out of 87 (32%) patients, the diagnosis made on referral to the specialist centre differed from the original. As paediatric tumours are less common and treatment effects potentially more damaging, specialist diagnostic expertise in referral centres is vital.…”
Section: Discussionmentioning
confidence: 99%